IMMUNITY AND INFECTION IN WOMEN WITH HYPERPLASTIC STATES OF IMMUNE SYSTEM - A. A. Lukach; O. A. Minyailo; V. I. Konovalov; A. I. Olkhovikov; N. V. Kungurov; N. M. Gerasimova; N. P. Evstigneeva; Ya. B. Beykin (Медицинская иммунология, 2014)
Abstract. One hundred and ninety-nine patients with hyperplastic processes of reproductive system were examined, and 131 (66.16%) of them were found to be infected with Chlamydia or Ureaplasma. The mean age of female patients was 42,7±1,35 years. Different infectious agents (e.g. Chlamydia trachomatis, Ureaplasma urealiticum, Mycoplasma hominis) were identified in cervical canal of uterine cervix and surgical specimens (biopsy samples of excised myoma, adenomyosis or endometrial hyperplasia). The infected patients were found to have decreased monocytes and neutrophils in blood counts, lower phagocytic activity of monocytes and neutrophils, and decreased bactericidal activity of leukocytes. Other findings included lower CD20+, CD8+ and rFAS CD 95 lymphocytes. Assessment of cytokine-synthesizing activity of CD3+ lymphocytes showed a decrease in both spontaneous and stimulated response (р < 0,001). A weakest spontaneous and stimulated response was found in CD3+/IL-4+ lymphocytes. Analysis of results obtained shows systemic immune disorders and impaired cytokine-synthesizing activity of CD3+ lymphocytes correlating with infection factors in the women with hyperplastic processes of reproductive system. (Med. Immunol., 2008, vol. 10, N 2-3, pp 223-228).